Fluorine depth profiles in human enamel after different acid etching times - Sampson W.J; Wookey C. W.; Rouse J. (Sciendo, 1987)
This study was designed to monitor fluorine concentration changes in the surface layer of enamel subjected to acid etching for orthodontic direct bonding. Prior to etching, the area described by the reference pins was partitioned into quadrants and initial fluorine concentration profiles in the surface 4 μm were recorded using a non-destructive nuclear resonance technique. Measurements of enamel surface location were made, relative to the reference pins, prior to etching and after 15,30, 60 and 120 seconds exposure to Superbond gel etchant. Each quadrant was then re-profiled for fluorine concentration. The measuring technique, therefore, provided information regarding etching depth (surface loss) and fluorine change in each of the quadrants.